Korpusnaja lingvistika, častotnaja i tolkovaja leksikografija - Mečkovskaja, Nina Borisovna (Slavistična revija, 2025)
With the overall growth in the number of corpora, their volumes and diversity, there is a specialization of corpora depending on their targeted content. Electronic corpora of the first generation (with a volume of approximately 100-million-word tokens), called or perceived as “national” or “state”, retain a relative balance of subcorpora and a broad social science and humanities audience. As the volumes of later corpora increase, there is a specialization of their purpose along two vectors: 1) content-oriented monitor (replenished) megacorpora of newspaper and magazine texts; the target groups of corpus content of this class include sociologists and political scientists, economists, demographers, journalists, etc. 2) thematically unlimited (non-selective) corpora accumulating digitalized texts (printed and electronic) used in computer science as raw material for “natural language processing” (machine pre-training 436 Slavistična revija, letnik 73/2025, št. 3, julij–september of neural networks) and creation of statistical algorithms for self-linking words into adequate verbal responses of artificial intelligence. Two most significant innovative developments in corpus lexicography are named: 1) synthesis of explanatory and frequency dictionaries in the Macmillan dictionaries (2007) and later Collins, Longman; 2) component semantic analysis of a 100,000-word dictionary using the 2,500 most frequent lexemes in Macmillan (2007) as semantic components
Keywords: frekvenčni slovarji; frequency dictionaries; high-frequency words as semantic multipliers; komponentna pomenska analiza 100.000-besednega slovarja; semantic component analysis of a 100,000-word dictionary; sinteza razlagalnih in frekvenčnih slovarjev v slovarjih Macmillan (2007); synthesis of explanatory and frequency dictionaries in the Macmillan dictionary (2007); visokofrekvenčne besede kot semantični multiplikatorji